Stress Alternation in English Morphological Derivation Words Produced by Native Speakers of Indonesia - RUDHA WIDAGSA (Journal of English Language Teaching and English Linguistics, 2016)
Although English students (English-L2) are allowed to retain their local accent when speaking English, they may not be intelligible if they use inappropriate stress in communication. This research is intended to find out how English-L2 produce stress in English morphological derivation words. The respondents of this study are 10 students of English Department (PBIUPY) Who are native speakers of Indonesian. PRAAT software is applied to analyse the recordings, including measuring the pitch of each word, the highest pitch indicates the primary or strongest stress in each word. The instruments of this study are 5 morphological derivation words which have different level and variation of stress. The result illustrates that English-L2 produce inappropriate stress alternation in English morphological derivation words. Most English-L2 are not able to distinguish between strong and weak stressed syllables. It is proved by the pitch which they produce have a broadly simillar pattern. Keywords: stress, alternation, English-L2